Alterations in gait parameters with peripheral artery disease: The importance of pre-frailty as a confounding variable. (December 2016) - Toosizadeh, Nima; Stocker, Hannah; Thiede, Rebecca; Mohler, Jane; Mills, Joseph L; Najafi, Bijan
Although poor walking is the most common symptom of peripheral artery disease (PAD), reported results are inconsistent when comparing gait parameters between PAD patients and healthy controls. This inconsistency may be due to frailty, which is highly prevalent among PAD patients. To address this hypothesis, 41 participants, 17 PAD (74±8 years) and 24 aged-matched controls (76±7 years), were recruited. Gait was objectively assessed using validated wearable sensors. Analysis of covariate (ANCOVA) tests were used to compare gait parameters between PAD and non-PAD groups, considering age, gender, and body mass index as covariates, while stratified based on frailty status. According to the Fried frailty index, 47% of PAD and 50% of control participants were non-frail and the rest were classified as pre-frail. Within non-frail participants, gait speed, body sway during walking, stride length, gait cycle time, double-support, knee range of motion, speed variability, mid-swing speed, and gait initiation were significantly different between PAD and control groups (effect size d = 0.75±0.43). In the pre-frail group, however, most of the gait differences were diminished except for gait initiation and gait variability. Results suggest that gait initiation is the most sensitive parameter for detecting gait impairment in PAD participants when compared to controls, regardless of frailty status ( d = 1.30–1.41; p <0.050). The observed interaction effect between frailty and PAD on gait parameters confirms the importance of assessing functionality in addition to age to provide more consistency in detecting motor performance impairments due to PAD.